Impact of empowerment and ICT on quality of work life: The mediating effect of trust climate - Kaniz Marium Akter; Swee Mei Tang; Zurina Adnan (Cogent Business & Management, 2023)
Aim of the study is to examine the impact of employee empowerment and ICT support on the employees' work life quality with the mediating effect of the hospitality firms' trust climate. Operational employees (n = 123) of the three star hotels of Bangladesh participated in the study. A partial least squares structural equation model (PLSSEM) was utilized in order to test a hypothesized model. Data were validated by a measurement model and hypotheses were tested by a structural equation model using the SmartPLS 3.0 software. Results indicate that climate of trust partially mediates the relationship between employee empowerment and quality of work life, and ICT support and quality of work life. The study also found that employee empowerment (Ø = 0.299), ICT support (Ø = 0.326), and climate of trust (Ø = 0.192) have strong effects (p < .05) on employees' quality of work life with a variance (R2) of 42.1%, while employee empowerment (Ø = 0.358) and ICT support (Ø = 0.393) have significant influences (p < .05) on firm's climate of trust with a variance (R2) of 38.1%. These findings may be utilized cautiously since the study was undertaken on the operational employees of the three star hotels in Bangladesh. This study provides new insights by defining the role of the hospitality firms in enriching the operators' life at work and the strategies that the hospitality managers can formulate to empower their staff, allow them effective technological support, and build an atmosphere with mutual trust for attaining positive employee focused outcomes.
Keywords: 650; climate of trust; employee empowerment; hospitality industry; ICT support; operational employees; quality of work life; three-star hotels